Activation of the phosphoenolpyruvate carboxykinase gene retinoic acid response element is dependent on a retinoic acid receptor/coregulator complex. - Hall, R K (1992)
The accessory factor 1 (AF1) element is an upstream transcriptional control region that plays a role in the response of the phosphoenolpyruvate carboxykinase (PEPCK) gene to both glucocorticoids and retinoic acid. We demonstrate here that retinoic acid receptor alpha (RAR alpha) binds to a sequence within the AF1 element, TGACCT (site B), that is a consensus retinoic acid response element (RARE) half-site. A similar DNA sequence, TGGCCG (site C), located 1 bp downstream of site B, is not involved in the binding of RAR alpha monomers or dimers but is required for the constitution of a functional RARE. Site C is also required for the formation of a complex involving RAR alpha and a liver nuclear factor designated CR, for coregulator. Mutational analysis of the AF1 element shows that the RAR alpha/CR complex is the trans-acting unit that mediates the retinoic acid response of the PEPCK gene. Another member of the retinoid receptor family, retinoid X receptor alpha (RXR alpha), can also form a complex with RAR alpha and the AF1 element. Several observations, including the observation that RXR alpha antibody interacts with CR, indicate that RXR alpha and CR are identical or closely related proteins. Through RXR alpha forms a complex with RAR alpha and the AF1 element, we demonstrate that the AF1 element is functionally distinguishable from a retinoid X response element. Taken together, our results show that the AF1 element contains an RARE that mediates a retinoic acid response by binding an RAR alpha/coregulator complex; this coregulator is presumably RXR alpha.